An EFL Teacher’s Voice on The Inculcation of Character Values - Lucky Rahayu Nurjamin; Ghia Aulia Syafitri (Ma'soem University, 2021)
As the significant effect of the appliance of character values in educational process, the EFL teaching and learning must be one of the medium in inculcating the points. However, the practice is still in a big question since many teachers, English teachers in particular, found the character values were hard to employed. Thus, this study focused on investigating an EFL teacher voice toward the inculcation of the character values. The participant involved in this case study was one of English teacher in tenth grade who had seventeen-year experience in teaching English. The data were collected using a semi-structured interview and document in the form of lesson plan. The result shown that, first, the teacher put the character values on the lesson plan representing the teacher follows the government’s suggestion in arranging 2013 curriculum lesson plan. Second, the teacher has a good understanding toward the importance character values as implied in teaching English. Third, the teacher prefer to use implicit strategy in inculcating the values as in line with the English material or instruction given.